Exploring user experience: A qualitative analysis of the use of a physical activity support app for people with heart failure - Andreas Blomqvist; Anna Strömberg; Marie Lundberg; Maria Bäck; Tiny Jaarsma; Leonie Klompstra (PLoS ONE, 2025)
Introduction Heart failure (HF) is a prevalent and debilitating global health issue, affecting approximately 65 million people worldwide. Physical activity is recommended for HF management, yet many people with HF remain sedentary. This study explored user experiences with an mHealth tool called the Activity Coach (the app), designed to support physical activity among people with HF. Purpose The purpose of this study was to describe users’ experiences with an app designed for supporting physical activity in people with HF. Methods Using a qualitative design, semi-structured telephone interviews were conducted with ten people with HF who used the app for 12 weeks. Thematic analysis was used to analyse the data. The interviews were transcribed verbatim, data items identified and coded and themes were generated based on these codes. The themes were subsequently defined and described. Results The analysis yielded two themes: “Cultivating awareness of physical activity engagement” and “Motivation through enjoyment in the monitoring process and through physical and emotional changes”. We found that while the app was found easy to use, users faced challenges in defining and tracking physical activity. The app increased users’ awareness and motivation for physical activity and helped establish new routines. Users also experienced improved physical health and emotional well-being. Conclusions The app created physical activity awareness and motivation, and the study shows that mHealth may be used to increase physical activity motivation and engagement in people with heart failure.